Normal Values of Spleen Stiffness in Healthy Volunteers and Effect of Meal on Liver Stiffness and Spleen Stiffness - Natrada Luekiatphaisan; Natthaporn Tanpowpong (Journal of Medical Ultrasound)
Background: The portal hypertension leads to variceal bleeding. Spleen stiffness (SS) is useful in estimating esophageal varices risk and less invasive as compared with reference standard method (hepatic venous pressure gradient). Using different methods of ultrasound elastography as well as different novel system provide different value of SS. Methods: After the approval by the institutional review board, we enrolled volunteers aged over 18 years who had no obesity, excessive alcohol use, history of systemic disease, hepatobiliary disease, or malignancy. Spleen and liver stiffnesses were measured with LOGIQ E10 SWE by two radiologists. Volunteers ingested a 460 kcal liquid meal. The spleen and liver stiffnesses were performed at baseline and 60, 120 and 180 min after meal. Results: A total of 46 volunteers participate and two volunteers were excluded. The mean SWE SS was 12.6 ± 1.18 kPa. There was no statistically significant difference between sex, age and spleen size. SS trends to decrease with time. In first 2 h after meals, there was no significant difference from baseline. After 3 h, SS significantly decreased from baseline. In contrast, liver stiffness trend to increase with time and significant elevate from baseline at 3 h. Intraclass correlation coefficient between the two radiologists showed fair agreement for SS and substantial agreement for liver stiffness. Conclusion: Our outcomes may be a reference value for evaluating SS in patients with other illnesses in clinical setting the utilize SWE with LOGIQ E10. SS decreased with time after a meal in normal volunteers and significant difference at 3 h. In contrast, liver stiffness increases with time after a meal in normal volunteers and significant difference at 3 h. There is importance of the operator’s expertise in SWE measurement should be considered for SS.